Eco-toxicity and health risk assessment of polycyclic aromatic hydrocarbons in surface sediments of Burullus Lake in Egypt - Hanan E Osman; Mohamed H E El-Morsy; Hazem T Abd El-Hamid (China Geology, 2024)
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental contaminants of growing concern due to their potential ecological and human health risks. This study presents a comprehensive assessment of PAHs contamination in the surface sediments of Burullus Lake, a vital and second largest delta lake in Egypt. The aim was to evaluate the eco-toxicity and potential health risks associated with the presence of these compounds. Surface seven sediment samples were collected from various drains in the southern part of Burullus Lake. Soxhlet extraction method was employed to extract PAHs (16PAHs) from the sediment sample. Analytically, target compounds were located using HPLC. The results showed that samples contained PAHs levels ranging from 0.038×10–6 to 0.459×10–6, which is considered heavily polluted by the European standard for PAHs pollution. Additionally, there was no apparent source of PAHs in the El-Khashah drain or the Brinbal Canal, as HPLC found none of the compounds. The most prevalent compound in sediment samples along the study area was fluoranthene. The diagnostic indices in the present study indicated that the hydrocarbons in the region originated from pyrolytic and man-made sources along the drains of Burullus Lake. The principal component analysis (PCA) and diagnostic ratios revealed that coal combustion and pyrolytic sources were responsible for the PAHs contamination in the surface sediments. The non-carcinogenic risk (HI), which is the product of the HQs for the adult and child populations, respectively, was calculated. HI values under 1, therefore, demonstrated that they had no carcinogenic effects on human health. TEQs and MEQs in the sediments of Burullus Lake do not have a cancer-causing impact on people. For the safety of nearby wildlife, aquatic life, and people, all activities that raise petroleum hydrocarbon levels in Burullus Lake must be adequately regulated and controlled. According to the ecological risk assessment, there is little chance that PAHs will be found in the sediments of Burullus Lake. This study underscores the urgent need for effective pollution control measures and regular monitoring of PAHs levels in Burullus Lake sediments to protect the aquatic ecosystem and public health. It also highlights the importance of considering eco-toxicity and human health risks in integrated risk assessments of PAHs-contaminated environments.